General Programmable Growth of Hybrid Core–Shell Nanostructures with Liquid Metal Nanodroplets. Issue 11 (1st February 2021) - Ren, Long; Cheng, Ningyan; Man, Xingkun; Qi, Dongchen; Liu, Yundan; Xu, Guobao; Cui, Dandan; Liu, Nana; Zhong, Jianxin; Peleckis, Germanas; Xu, Xun; Dou, Shi Xue; et al.
Abstract: Core–shell and hollow nanostructures have been receiving significant interest due to their potential in wide scientific and technological fields. Given such large scope, however, they still lag far behind in terms of the ambition toward controllably, or even programmatically, synthesizing libraries of core–shell structures on a large scale. Here, a general route for the programmable preparation of complex core–shell nanostructures by using liquid metal (LM) droplets as reformable templates is presented, and the triggering of a localized galvanic replacement reaction in one ultrasonication system is demonstrated. Benefiting from the activity and mobility of the metal components in LM templates, high‐level compositional diversity control and quantitative regulation of both the core and the shell layers of the heterogeneous products are achieved, which cannot be realized with a solid‐template synthetic route. Abstract : A general programmable strategy to fabricate core–shell nanostructures by using liquid metal nanodroplets as reformable core templates is demonstrated, offering a route to producing nanostructures with multiple, complex, and desired structures, compositions, and sizes on a large scale.